Comparison Of Islamic Law And Positive Law On Violence In The Name Of Religion In Terrorism Cases - Zarkasih, Muhamad (JURNAL USM LAW REVIEW, 2023)
The purpose of this study is to determine the legal regulation of violence in the name of religion that contains elements of radicalism, extremism and terrorism in terms of comparative Islamic law and positive law in Indonesia. Radicalism, extremism and terrorism are like three things that go hand in hand, these three are a frightening specter for most of humanity, especially in the Unitary State of the Republic of Indonesia. This research is a type of normative research. The approach used in this study is a statutory and conceptual approach. The results of the study show that in the perspective of Islamic law, behavior that gives birth to extreme understanding by expressing it through violence in order to maintain its ideology can be considered as al-baghy (rebel). Article 43D paragraph (2) letter f of Law no. 5 of 2018 which explains that what is meant by "people or groups of people who have been exposed to radical ideas of terrorism" are people or groups of people who have a radical understanding of terrorism and have the potential to commit acts of terrorism. There are four characteristics of extremists, including making it difficult for themselves to do good, being rude and harsh, easy to disbelieve, and being fanatical about Madzhab and not wanting to follow other opinions. Extremist acts of violence in the name of religion can be punished in accordance with article 170 of the Criminal Code which contains such acts can be punished according to Indonesian law in Article 170 of the Criminal Code. MUI in its fatwa on terrorism views that carrying out acts or acts of terror is unlawful, whether carried out by individuals, groups, or the state. The crime of terrorism is regulated in Law no. 5 of 2018. The criminal threats for perpetrators of terrorism are: imprisonment between 3 to 20 years, life imprisonment or the death penalty.